Prevalence of sarcopenia and its association with frailty and malnutrition among older patients with sepsis-a cross-sectional study in the emergency department - Qiujing Li; Na Shang; Qian Gao; Shubin Guo; Tiecheng Yang (BMC Geriatrics)
Abstract Background Studies on the prevalence of sarcopenia and its relationship with other geriatric syndromes among older patients with sepsis in the emergency department (ED) are scarce. This study aimed to investigate the prevalence of sarcopenia among older patients with sepsis and explore its association with specific geriatric symptoms: frailty and malnutrition. Methods This cross-sectional study was carried out in China from January to November 2022. Muscle mass, as indicated by the skeletal muscle index (SMI) was measured using abdominal plain computed tomography. Sarcopenia, frailty, and nutritional status were defined according to the Asian Working Group for Sarcopenia 2019 criteria, Clinical Frailty Scale (CFS) score, and Mini Nutritional Assessment-Short Form (MNA-SF) score. The correlations of the SMI with the CFS and MNA-SF scores were analyzed using nonparametric Spearman correlation analysis. Univariate and multivariable logistic regression analyses were performed to determine the associations of sarcopenia with frailty and malnutrition. Results A total of 602 patients (332 men; median age, 78 years; median body mass index, 23.1 kg/m2) were included. Sarcopenia, frailty, and malnutrition were present in 36.2%, 58.0%, and 34.6% of the patients, respectively. Of the 602 patients, 414 (68.8%) had at least one geriatric syndrome, 253 (42.0%) had at least two simultaneously. The SMI correlated negatively with the CFS score and positively with the MNA-SF score (all p < 0.001). The CFS (adjusted odds ratio [OR] = 1.384 per 1-point increase, p < 0.001) and MNA-SF (adjusted OR = 0.887 per 1-point increase, p = 0.002) scores were independently associated with sarcopenia. Frailty (adjusted OR = 3.816, p = 0.003), being at risk of malnutrition (adjusted OR = 2.466, p = 0.001), and being malnourished (adjusted OR = 2.477, p = 0.002) were independently associated with sarcopenia. Conclusions Sarcopenia and coexisting geriatric syndromes were prevalent and interrelated among older patients with sepsis in EDs. Clinicians should assess older patients with sepsis for geriatric syndromes to provide them with more accurate interventions. Trial registration This study was registered at www.chictr.org.cn (registration number: ChiCTR2300070377, date: 11–04-2023).